Pembaruan Ilmu Balaghah dalam Pemikiran Ahmad Asy-Syayib melalui Karyanya Al-Uslub - M. Irwan Jayadi; Raswan; Ahmad Dardiri; Achmad Fudhaili (Lembaga Pengkajian Pengembangan Pendidikan dan Kewirausahaan, 2025)
This study examines the reformist thought in the science of Arabic rhetoric (balaghah) proposed by Ahmad Asy-Syayib through his seminal work Al-Uslub. Utilizing a library research approach with critical content analysis, the study explores Asy-Syayib’s innovative framework in reinterpreting balaghah, particularly through the incorporation of psychological dimensions, the principle of mu?abaqah (correspondence between meaning and expression), and the intrinsic connection between linguistic style and individual character. His approach bridges the classical rhetorical tradition with modern perspectives, without disregarding the intellectual legacy of the past. The reform is intended to render balaghah more relevant within the realms of contemporary literary and communication studies. Despite facing some criticism, his ideas are regarded as a significant alternative foundation for the development of modern Arabic rhetorical studies.